Scientific Literacy Assessment for Physics Instruction by Integration Local Wisdom of Mandar Tribe in West Sulawesi, Indonesia - Sartika, Dewi; Nurlina, Nurlina; Mutmainna, Mutmainna (STKIP Singkawang, 2025)
Scientific literacy is an important skill that enables students to apply scientific knowledge to solve daily problems. However, Indonesian students’ scientific literacy levels are still relatively low compared to international standards. One potential strategy to address this issue is integrating local wisdom into science learning. This study aims to develop a scientific literacy assessment instrument based on local wisdom that meets the eligibility criteria to improve students’ scientific literacy skills comprehensively. Using a research and development (R&D) methodology, this study was conducted in three main stages: product design, product trial, and product assembly. The instrument underwent expert validation and was tested on a limited and larger scale to evaluate readability, item difficulty, item discrimination, and reliability. The findings indicate that the instrument is valid, reliable, and effective for assessing students’ scientific literacy. It helps educators diagnose students’ abilities to communicate, associate, and apply scientific concepts in real-life and culturally relevant contexts. By connecting science learning with students’ cultural backgrounds, this study contributes to enhancing the quality of physics education and improving scientific literacy outcomes among Indonesian students.